Compost-formulated Media for Foliage Plant Production - Jianjun Chen; Dennis B. McConnell (EDIS, 2002)
This document is ENH873, one of a series of the Environmental Horticulture Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date September 11, 2002.